2004
DOI: 10.1111/j.1365-2133.2004.06172.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olopatadine hydrochloride, an antihistamine drug, on skin inflammation induced by repeated topical application of oxazolone in mice

Abstract: These results indicate that olopatadine is an antihistamine agent having inhibitory activities against chronic inflammatory dermatitis, possibly resulting from its diminishing effect on elevated cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
3
29
0
2
Order By: Relevance
“…In the present study, CA and AHAL significantly suppressed the ear edema and the increased level of IFN-g, a Th1 cytokine that activates various types of cells resulting in inflammatory events and the induction of skin hypertrophy due to an increase in keratinocyte proliferation. 35,36) In this context, a previous study described the antiproliferative activity of 12-acetoxy-hawtriwaic acid lactone on cell growth of human cell line, CCD922 normal skin fibroblasts. 37) In conclusion, we provided in vivo evidence to show that the diterpenes from Egletes viscosa are effective topical antiinflammatory agents in the experimental models of acute or chronic dermatitis and suggest that these may serve as lead compounds for developing drugs effective in skin inflammatory disorders like atopic or contact dermatitis and in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, CA and AHAL significantly suppressed the ear edema and the increased level of IFN-g, a Th1 cytokine that activates various types of cells resulting in inflammatory events and the induction of skin hypertrophy due to an increase in keratinocyte proliferation. 35,36) In this context, a previous study described the antiproliferative activity of 12-acetoxy-hawtriwaic acid lactone on cell growth of human cell line, CCD922 normal skin fibroblasts. 37) In conclusion, we provided in vivo evidence to show that the diterpenes from Egletes viscosa are effective topical antiinflammatory agents in the experimental models of acute or chronic dermatitis and suggest that these may serve as lead compounds for developing drugs effective in skin inflammatory disorders like atopic or contact dermatitis and in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine and H 1 receptor-mediated events have been found to play a key role in the development of eczematous lesions in experimental dermatitis in mice [24,28,33]. Seike et al [33 ]reported that histamine-deficient (histidine decarboxylase gene knockout) mice failed to develop diphenylcyclopropenone (DCP)-induced contact dermatitis, and this phenomenon was corrected by treatment with an H 1 receptor agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports provided evidence for the pleiotropic effects of olopatadine: amelioration of the damaged skin barrier function [34], stabilization of mast cells [35], inhibition of monocyte migration [36], and improvement of inflammation and scratch behavior in oxazolone-evoked chronic dermatitis [28,29]. Of course, the therapeutic effects of olopatadine (reduced inflammatory cell infiltrates, cytokines and histamine) might result from the complex combination of these events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most of these fi ndings are also observed in patients with AD, the mouse models appear to mimic many, if not all, events occurring within the lesioned skin of patients with AD. We recently have reported that olopatadine mitigates the cutaneous infl ammation in a mouse model of chronic infl ammatory dermatitis induced by repeated challenge of hapten to the ear [13] .…”
mentioning
confidence: 99%